Improving teaching–learning process through ICT methods assisted with CFD techniques for marine engineering courses. Issue 2 (17th December 2013) - Gutiérrez, J.E.; Zamora, B.
ABSTRACT This article presents a teaching–learning methodology for the subject "Hydrodynamic, Resistance and Propulsion" in the Degree of Naval Architecture. A new teaching approach is proposed, for ensuring that students acquire skills related to the ability of analyzing and designing different types of ships. The roles of both Information and Communication Technologies (ICT) and Computational Fluid Dynamics (CFD) methods are some specific features of the methodology. © 2013 Wiley Periodicals, Inc. Comput Appl Eng Educ 23:239–249, 2015; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21592